2017
DOI: 10.21873/anticanres.11624
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Circulating Tumor Cells and Annexin A2 in Early Breast Cancer Patients

Abstract: ANXA2 stromal expression might play a key role in aggressive tumor phenotype associated with increased EMT CTCs release, however, other factors beyond ANXA2 are responsible for coagulation activation mediated by CTCs in breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…These vimentin-positive/cytokeratin-negative cells might be cancer cells that have undergone epithelial-to-mesenchymal transition, although the absence of cytokeratin expression suggests that they are likely to be fibroblast-like cells (CTCs are typically defined as cytokeratin-positive). Interestingly, stromal annexin A2 expression was higher in the tumours of patients who had a majority of CTCs with a mesenchymal phenotype than in those with a majority of epithelial-like CTCs 156 . These data suggest that circulating CAFs might have a role in the metastatic process, as they are found in patients with metastatic disease at a higher rate than those with localized disease.…”
Section: Stroma–cancer Interactionsmentioning
confidence: 93%
“…These vimentin-positive/cytokeratin-negative cells might be cancer cells that have undergone epithelial-to-mesenchymal transition, although the absence of cytokeratin expression suggests that they are likely to be fibroblast-like cells (CTCs are typically defined as cytokeratin-positive). Interestingly, stromal annexin A2 expression was higher in the tumours of patients who had a majority of CTCs with a mesenchymal phenotype than in those with a majority of epithelial-like CTCs 156 . These data suggest that circulating CAFs might have a role in the metastatic process, as they are found in patients with metastatic disease at a higher rate than those with localized disease.…”
Section: Stroma–cancer Interactionsmentioning
confidence: 93%
“…Survival analysis reveals substantially poor OS and DFS in patients with high Anxa2 expression 8 . Anxa2 could also be a secretory biomarker in the plasma samples of patients with breast cancer and thus is valuable for early diagnosis 9,10 . The triple negative (ER, PR, and HER2 negative) breast cancer (TNBC) is the most aggressive type usually detected with upregulated EGFR expression, and Anxa2 is reversely correlated with hormone receptors 11 and HER2 expression 12 but positively related with EGFR expression in breast cancer tissues 8 .…”
Section: Breast Cancermentioning
confidence: 99%
“…In 2016, Mangala et al described the selection of thioaptamers targeting ovarian cancer-associated endothelial cells generated by using a thioaptamer version of the Cell-SELEX technique [ 155 ] against ovarian cancer associated-endothelial cells derived from ten different patients while using cells derived from normal ovaries as controls. They found that the Endo28 thioaptamer targets annexin A2, a protein upregulated in cancer [ 156 , 157 ]. When Endo28 was conjugated to the surface of Chitosan (CH) Nanoparticles (NP) containing siRNA targeting micro-RNAs miR106b-5p and miR30c-5p, the CH/Endo28-siRNA-NP provided enhanced targeting of the tumor relative to other organs.…”
Section: Thioaptamer Developmentmentioning
confidence: 99%